Physics-based thermal model for power gearboxes in geared turbofan engines - Jafari, Soheil; Nikolaidis, Theoklis; van Heerden, Albert S. J.; Lawson, Craig P.; Bosak, David (ASME, 2021)
Ultra-High Bypass Ratio Geared (UHBRG) turbofan technology allows a significant reduction in fuel burn, noise and emissions — key metrics for aircraft engine performance. However, one of the main challenges in this technology is the large amount of waste heat generated by the Power Gearbox (PGB). Therefore, having a practical tool for precise prediction of the PGB-generated thermal loads in UHBRGs is becoming a necessity. Such a tool would assist in analyzing engine performance, as well as ensuring that engine physical limitations/restrictions are not breached (e.g. over-temperature in fuel and oil, cocking, etc.). This paper presents a methodological approach to mathematically model the waste heat generated by a PGB on a UHBRG for different points on a typical flight profile. To do this, the total power loss in a PGB system is firstly defined as the summation of load-dependent and load-independent losses. Physics-based equations for each heat loss mechanism are introduced and, through a combination of the associated equations, a simulation model for the thermal loads calculation in PGBs is developed. In addition, the heat losses and efficiency of the PGB has been analyzed across a simulated flight. The developed PGB model calculates the main power losses generated in a gear reduction system of a turbofan engine. It is found that in a typical flight, the heat loss generated by the PGB can reach about 80% of the total waste heat generated by the engine. The values of the mechanical efficiency calculated by the tool at different flight points are above 97% which is in good agreement with publicly available data for planetary gearboxes. This tool is intended to be utilized by engine thermal management system designers to predict and analyze the heat loads generated by the PGB at different flight conditions
Keywords: Thermal management; Simulation models; Noise (Sound); Mechanical efficiency; Mechanical drives; Gears; Emissions; Aircraft engines; Turbofans